Occupational exposure to polycyclic aromatic hydrocarbons and cognitive impairment: Protocol of a systematic review - Prakasit Tonchoy; Nestor Asiamah; Rufus Akintimehin; Pannawadee Singkaew (PLoS ONE, 2025)
Occupational exposure to polycyclic aromatic hydrocarbons (PAHs) has been associated with adverse health effects, yet evidence on the cognitive consequences of such exposure remains fragmented and has not been systematically synthesized across occupational groups. This protocol outlines a systematic review that will examine the relationship between occupational PAH exposure and cognitive impairment across eight predefined occupational categories. Relevant studies will be identified through electronic searches of major databases, including PubMed, Web of Science, Scopus, Embase, ProQuest, PsycINFO, CINAHL, the Cochrane Library, and Google Scholar. Eligible studies must assess PAH exposure in occupational settings and evaluate cognitive outcomes using validated instruments, with domain-specific neuropsychological tests prioritized as primary outcomes and global screening tools (e.g., MoCA, MMSE) included as supportive outcomes. Both observational and comparative study designs will be considered. Titles and abstracts will be screened by two independent reviewers, and full texts of potentially eligible articles will be assessed using predefined criteria. Data will be synthesized narratively, with contingency meta-analysis conducted where sufficient comparable data are available and heterogeneity is acceptable. Prespecified subgroup analyses will be undertaken by occupational category, biomarker, cognitive domain, and exposure context, with meta-regression considered if an adequate number of studies are identified. Risk of bias will be assessed using JBI tools at the study level and ROBIS at the review level, with planned sensitivity analyses. The review will consolidate current evidence on PAH-related cognitive outcomes across occupational groups, including under-studied populations such as wildland firefighters, and will inform occupational health policy, workplace screening initiatives, and future research aimed at safeguarding cognitive health in exposed populations.